A strategy to reduce the twist defect in roll-formed asymmetrical-channel sections. (September 2018) - Tajik, Yaser; Moslemi Naeini, Hassan; Azizi Tafti, Roohollah; Shirani Bidabadi, Behrooz
Abstract: The most important step in designing the roll-forming processes is to design of a flower pattern. Currently, this is mostly done based on trial and error and the designer's experience. Using an optimized flower pattern, products with the intended dimensional- and geometrical-tolerance limits could be produced by a minimal number of forming stands. Twisting, which is a common defect in roll-formed asymmetrical-channel sections, affects the appearance and functionality of the product. In this research, the twist defect was studied by finite-element analysis for asymmetrical channels with different flange lengths. Some experiments were also performed on an industrial roll-forming machine to verify the accuracy of the finite-element model. The twist defect was observed to result from a torsional torque produced due to different forming forces applied to long and short flanges. Furthermore, in the roll-forming process of asymmetrical-channel sections, the strip is not deformed symmetrically and the long flange edge touches the roll before the short one. Therefore, the long flange is subjected to a forming force before the short flange. Since predicting the twist angle without costly trial and error in a workshop, or time-consuming finite-element simulations is desirable for the roll-forming industries, a simple relation was introduced considering the geometrical properties of asymmetrical-channel sections. Thereby, asymmetrical forming rolls were presented to form both flanges more symmetrically; a smaller twist defect is achieved. Highlights: Twist defect in the roll formed asymmetrical channels was investigated. Asymmetrical application of forces to the flanges makes twist defect in channel. Longitudinal strains distributions in flange zones were studied experimentally. Similar deformation of both flanges edges before the forming reduces twist defect.